2016
DOI: 10.1111/1755-5922.12193
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin attenuates sympathetic hyperinnervation together with the augmentation of M2 macrophages in rats postmyocardial infarction

Abstract: SummaryObjectives: Inflammation after myocardial infarction (MI) causes cardiac nerve sprouting and consequent ventricular arrhythmias (VAs). Macrophages, as major immune cells, are involved in the entire inflammation response process and serve as a link between inflammation and sympathetic hyperinnervation by regulating nerve growth factor (NGF) expression. Accumulating evidence shows that statins possess antiarrhythmogenic properties, and the aim of this study was to explore the mechanism by which atorvastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Fluvastatin pretreatment reversed these changes in SCG neurons caused by MI injury. Fluvastatin can reduce the electrical activity of SCG neurons, consistent with the results in clinical and experimental studies that statins decrease sympathetic activity and effectively ameliorate cardiac sympathetic nerve remodeling ( Kim et al, 2009 ; Lewandowski et al, 2014 ; Yang et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Fluvastatin pretreatment reversed these changes in SCG neurons caused by MI injury. Fluvastatin can reduce the electrical activity of SCG neurons, consistent with the results in clinical and experimental studies that statins decrease sympathetic activity and effectively ameliorate cardiac sympathetic nerve remodeling ( Kim et al, 2009 ; Lewandowski et al, 2014 ; Yang et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…Fluvastatin ameliorates cardiac sympathetic neural dysfunction in diabetic rats ( Matsuki et al, 2010 ). In addition, clinical and experimental studies have suggested that statins decrease sympathetic activity and effectively ameliorate cardiac sympathetic nerve remodeling ( Kim et al, 2009 ; Lewandowski et al, 2014 ; Yang et al, 2016 ), but its mechanism of direct protection actions on sympathetic nerve has not been fully characterized. In our experiments, the characteristics of the SCG including the electrical properties and mRNA expression of ion channels, as well as AP characteristics were significantly altered at different time points after MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atorvastatin treatment exceeded the benefits of lipid level reduction alone [ 20 ]. Numerous studies have demonstrated the beneficial role of atorvastatin in cardiac remodeling [ 21 ] and macrophage migration [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It shows up as a series of pathophysiological changes including myocardial denervation, nerve sprouting, sympathetic over-regeneration, and high domination, 5) ultimately developing into electrophysiological heterogeneity. 6) After the subacute period, fibrous and scar tissue replaces ischemic necrotic myocardium. The fibrous tissue could develop into regions of conduction block and form nonuniform anisotropy and slow conduction which may finally result in reentry substrate for sustained VAs.…”
mentioning
confidence: 99%